2007
DOI: 10.1016/j.aquatox.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to p,p′-DDE or dieldrin during the reproductive season alters hepatic CYP expression in largemouth bass (Micropterus salmoides)

Abstract: Largemouth bass (LMB) in Central Florida living on sites with high levels of organochlorine pesticides (OCPs) have exhibited poor reproductive success and altered steroid profiles. The mechanism underlying these changes is unknown, however changes in the rate of steroid metabolism could alter steroid homeostasis. Members of the CYP2 and CYP3A families play a significant role in the metabolism of many xenobiotics and endogenous compounds, including sex steroids. Therefore, the goal of this study was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Dietary exposure to technical DDT has reduced survival in fish at multiple life stages (see review by Jarvinen and Ankley, 1999), and protective thresholds for whole-body total DDT concentrations have been recommended for early life stage, juvenile, and adult fish (Beckvar et al, 2005). In addition, exposure to p,p 0 -DDE, o,p 0 -DDT, and o,p 0 -DDE can affect behavior and disrupt the endocrine and immune systems in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Faulk et al, 1999;Milston et al, 2003;Papoulias et al, 2003;GarciaReyero et al, 2006;Barber et al, 2007). Exposure to p,p 0 -DDE has been associated with reduced reproductive success of bird populations; bald eagle (Haliaeetus leucocephalus) and osprey (Pandion haliaetus) are especially susceptible to eggshell thinning after exposure (Anderson and Hickey, 1972;Wiemeyer et al, 1984Wiemeyer et al, , 1988.…”
mentioning
confidence: 99%
“…Dietary exposure to technical DDT has reduced survival in fish at multiple life stages (see review by Jarvinen and Ankley, 1999), and protective thresholds for whole-body total DDT concentrations have been recommended for early life stage, juvenile, and adult fish (Beckvar et al, 2005). In addition, exposure to p,p 0 -DDE, o,p 0 -DDT, and o,p 0 -DDE can affect behavior and disrupt the endocrine and immune systems in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Faulk et al, 1999;Milston et al, 2003;Papoulias et al, 2003;GarciaReyero et al, 2006;Barber et al, 2007). Exposure to p,p 0 -DDE has been associated with reduced reproductive success of bird populations; bald eagle (Haliaeetus leucocephalus) and osprey (Pandion haliaetus) are especially susceptible to eggshell thinning after exposure (Anderson and Hickey, 1972;Wiemeyer et al, 1984Wiemeyer et al, , 1988.…”
mentioning
confidence: 99%
“…Report also shows that there is correlation between low level of exposure to benzene, shortened gestation period and polymorphisms with susceptible gene [46]. There is significant high risk of PTD in women, who smoke and carrying genotype CYP1A1 along with GSTT1 [90]. It has also been suggested that there is increased risk of disease like lung, prostate cancer due to exposure of harmful chemicals like OCP and GST null genotype interactions [17,91].…”
Section: Gene Environment Interaction and Preterm Deliverymentioning
confidence: 99%
“…It has been reported that differential expression of CYP3A gene on chronic exposure to p,p′-DDE and dieldrin but the mechanisms is not yet clear. In mammals p,p′-DDE and dieldrin have been shown to induce CYP3A expression by activation of the constitutive androstane receptor and nuclear receptors in mammals [90]. Further, they have suggested that steroid hormones regulate the expression of CYPs.…”
Section: Correlation Between Ocps Level Inflammatory and Antioxidantmentioning
confidence: 99%
“…In addition to P450 enzymes, HepaRG cells have a stable expression of phase II enzymes, transporters and nuclear transcription factors over a time period of six weeks in culture (Aninat et al 2006;Anthérieu et al 2010;Kanebratt and Andersson, 2008;Turpeinen et al 2009). Both immunoblotting and reverse transcription polymerase chain reaction (RT-PCR) techniques have been applied to examine the pesticide-CYP induction (Wyde et al 2003;Lemaire et al 2004;Das et al 2006;Sun et al 2005;Johri et al 2007;Barber et al 2007). However, problems in tissue availability, interindividual differences, reproducibility and ethical issues preclude the efficient large-scale use of human primary hepatocytes for induction screening.…”
Section: Induction Of Cyp Enzymesmentioning
confidence: 99%